Rancang Bangun Sistem Informasi Manajemen Tugas Akhir Universitas Tabanan (Simantab) Berbasis Web Dan Mobile Menggunakan Framework Flutter - Dewi, Ni Made Ayu Krisna; Gunawan, I Made Agus Oka; Wiarsana, I Gede Sandi (Universitas Tabanan, 2024)
The impact of Covid-19 has been felt since March 2020 with restrictions on activities involving large groups of people. One of the activities that have been quite impacted by Covid-19 is the implementation of student Final Project activities, starting from the guidance process, administrative completeness and exams. The solution currently being carried out is that activities are carried out online using the Whatsapp platform and then manually recap the incoming data. This is certainly less efficient for its administrative management. Monitoring the progress of a student's final project by the Study Program, Faculty or University is also difficult to do. So it is necessary to develop a platform that can process student final project data management such as administrative data, final project progress and final project exams. Requirements specifications in the system built, are modeled using Data Flow Diagrams and Entity Relationship Diagrams. The implementation process of the application that is built is broken down into 2, namely web-based pages using the Laravel Framework and application-based using the Flutter framework. Code implementation is carried out on the Flutter framework, resulting in mobile-based applications and web-based applications. Flutter for the web uses Dart2js to compile Flutter code into Javascript. So it will be able to run on a web browser. Testing the functionality of each user's access to the system has been carried out properly using the blackbox testing method with results that are in line with expectations.